Effect of rootstock on cluster quality of ’Niágara Rosada’ table grape - Pauletto, Dário; Filho, Francisco de Assis Alves Mourão; Kluge, Ricardo Alfredo; Filho, João Alexio Scarpare (Pesquisa Agropecuaria Brasileira, 2001)
The aim of this paper was to evaluate the cluster quality of 'Niágara Rosada' table grape (Vitis labrusca L.) grafted on different rootstocks and evaluated during seven crops, at Taubaté, SP, Brazil. The clusters harvested in plants grafted with 'IAC 313', 'IAC 766' and 'Traviú' presented size (length and width), mass and number of berries significantly higher than those verified in plants grafted with 'Kober 5BB' and 'Schwarzmann'. The berry presented mass significantly higher in the 'IAC 766' and 'Traviú' if compared to the 'Schwarzmann'. Fruit soluble solid content was higher in 'Kober 5BB' (15.46oBrix) and 'Schwarzmann' (15.28oBrix) if compared to the 'IAC 313' (14.18oBrix).